PENGARUH KREDIBILITAS KONTEN WORKOUT DI YOUTUBE CHANNEL YULIA BALTSCHUN TERHADAP PEMBENTUKAN SIKAP POSITIF GENERASI Z UNTUK BEROLAHRAGA (SURVEI PADA MAHASISWI AKTIF UPN VETERAN JAKARTA) - Indriana Safira (2023)
The rapid development of social media YouTube in Indonesia is exploited by fitness influencers to convey information and experiences through workout content. The application of source credibility has been a contributing factor to a person's attitude change. The research aims to find out the impact of the credibility of workout content on Yulia Baltschun's YouTube channel on the formation of a positive attitude toward exercise among the Z generation. This research theory uses the theory of source credibility. This research uses explanatory quantitative methods with sampling techniques performed by a purposive sampler. The research method used was a survey of 94 active UPN veterans in Jakarta. The results of the study have influenced the credibility of workout content on Yulia Baltschun's YouTube channel and the formation of a positive attitude toward exercise among the Z generation. The size of the influence given by the credibility of the workout content of 56.1% on the formation of a positive attitude of Generation Z toward exercise The remaining 43.9% were influenced by variables outside the scope of this study.